Husband involvement in antenatal care moderates the link between vitamin D status and depressive symptoms in pregnant women - Rosa S. Wong; Keith T. S. Tung; Hing Wai Tsang; Jennifer K. Y. Ko; Wing-cheong Leung; Patrick Ip (Epidemiology and Psychiatric Sciences)
Abstract Aims The association between a pregnant mother’s vitamin D status and depressive symptoms has yielded inconsistent results. It is possible that other factors play a role in this association, as depression can have multiple causes. Recognizing the significance of the husband’s participation in antenatal care, this study aimed to examine whether the husband’s involvement moderates the link between the mother’s vitamin D status and depressive symptoms during pregnancy.